Zarządzanie konkurencyjnością w przedsiębiorstwach Doliny Lotniczej - w świetle badań empirycznych - Bembenek, Bogusław (Competitiveness Management in Enterprises of Aviation Valley - in the Light of Empirical Research, 2008)
The article is an attempt of introducing the impact of changes in enterprise's environment on enterprise competitiveness building process. The author underlines the thinking and running business by enterprises of Aviation Valley, bay analysing this issue from the point of view of surviving in stormy environment. The article presents the idea of competitiveness management in enterprises of Aviation Valley.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 20, s. 30-38